Difference in postoperative opioid consumption after spinal versus general anaesthesia for ankle fracture surgery—A retrospective cohort study. Issue 8 (20th May 2021) - Lehto, Pasi M.; Vakkala, Merja A.; Alahuhta, Seppo; Liisanantti, Janne H.; Kortekangas, Tero H. J.; Hiltunen, Kaisu; Nyman, Emma‐Sofia; Kaakinen, Timo I.
Abstract: Background: Surgical treatment of ankle fracture is associated with significant pain and high postoperative opioid consumption. The anaesthesia method may affect early postoperative pain. The main objective of the study was to compare postoperative opioid consumption after ankle‐fracture surgery between patients treated with spinal anaesthesia and general anaesthesia. Methods: We reviewed retrospectively the files of 586 adult patients with surgically treated ankle fracture in the years 2014 through 2016. The primary outcome was opioid consumption during the first 48 postoperative hours. Secondary outcomes were maximal pain scores, postoperative nausea and vomiting, the length of stay in the post‐anaesthesia care unit, and opioid use in different time periods up to 48 h postoperatively. Propensity score matching was used to mitigate confounding variables. Results: Total opioid consumption 48 h postoperatively was significantly lower after spinal anaesthesia (propensity score‐matched population: effect size −13.7 milligrams; 95% CI −18.8 to −8.5; P  < .001). The highest pain score on the numerical rating scale in the post‐anaesthesia care unit was significantly higher after general anaesthesia (propensity score‐matched population: effect size 3.7 points; 95% CI 3.2‐4.2; P  < .001). A total of 60 patients had postoperative nausea and vomiting in the post‐anaesthesia care unit, 53 (88.3%) of whom had general anaesthesia ( P  = .001). Conclusions: Patients with surgically treated ankle fracture whose operation was performed under general anaesthesia used significantly more opioids in the first 48 h postoperatively, predominantly in the post‐anaesthesia care unit, compared with patients given spinal anaesthesia.